Analysis of Aggressive Behavior Studies in the Workplace in Indonesia: A Systematic Literature Review - Setyawan, Jefri; Agung Rian Asmoro (HM Publisher, 2024)
Aggressive behavior in the workplace is a crucial issue in Indonesia, potentially having a negative impact on individuals, teams, and organizations. This systematic literature review aims to analyze research on aggressive behavior in the workplace in Indonesia, including the factors that influence it, its impact, and coping strategies. This literature review uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. A literature search was conducted in electronic databases such as Google Scholar, Scopus, and PubMed with the keywords